(untitled) (Politeja, 2020)
The identity of subjects participating in social processes or the daily functioning of social structures is a result of many factors – such as their representativeness and social typicality, the social programming of their personalities and activities, but also their personal experiences and individual characteristics. Formal expressions and testimonies of identity associated with the sense of belonging to a group, ideological belonging, are unreliable. An objectified and effective test of the real identity of an individual as a member of society, citizen, employee, follower of certain views, is the model of authenticity in participation. The components of this model include the criteria of authenticity of existence, authenticity of bonds and social structures, authenticity of the status of participants, authenticity of their needs, authenticity of attitudes, actions and works. Authenticity in this meaning is not the same as simply being authentic, or factual, genuine, original or consistent in reference to the original, or as a testimony’s conformity with the facts. It is a combination of such traits as autonomy, autotelic quality, consistency, functionality of the relationship between the whole and its elements, while, in relation to human consciousness and activity – sincerity, spontaneity, adequacy in relation to one’s own needs and nature.